ANALISIS STRATEGI TERHADAP KOMPETISI PADA HOTEL JAYAKARTA DAIRA PALEMBANG - Noviarni .; Maswah . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
This study aims to know the benefit of SWOT analysis to the competitive strategy at the Jayakarta Daira Palembang By using SWOT analysis it can help the company to form the right strategy in raising the position of this hotel. The population is the Jayakartaa Daira Hotel Palembang The sample of this study is company’s report in the form of e-mail start from Desember Until February.Analysis technique in this study is descriptive qualitative analysis. It describe about the problem that will be discussed base on the theories that relates with the problem in the Jayakarta Daira Hotel Palembang clearly. The result of data analysis show that the Jayakarta Daira Hotel Palembang has good velue at internal environment. The value of Strangths position is 31% it’s bigger than Weaknesses position with 26%. At the external environment, value for Opportunities is 23 %, it’s bigger than Threats that has 20 %. By the analysis result that is done by the authors, it can be conclude that SO Strengths- Opportunitties) strategy is more right to be applied at supports the aggressive strategy that reach the opportunities by using its own strengths. Keywords : Competitive strategy, descriptive qualitative